The Effect of Job Satisfaction and Employee Personality on Employee Performance with Organizational Citizenship Behavior as a Mediation (Empirical Study at Pandanaran University) - Dheasey Amboningtyas; Sinta Petri Lestari; Andi Tri Haryono; Leonardo Budi Hasiholan (Jurnal Multidisiplin Sahombu, 2026)
This study aims to test and analyze the effect of job satisfaction and employee personality on employee performance with organizational citizenship behavior as a mediation (Empirical Study at Pandanaran University). The population in this study were all permanent employees of Pandanaran University. The study was conducted using SPSS analysis tools. The results of the study showed that job satisfaction positively affects team member performance. Team member personality does not affect team member performance. Job satisfaction positively influences organizational citizenship behavior. Team member personality has a positive effect on organizational citizenship behavior. Organizational citizenship behavior positively impacts team member performance. Organizational citizenship behavior mediates the relationship between job satisfaction and team member performance. Organizational citizenship behavior mediates the effect of team member personality on team member performance.